Comparison of the vitamin D level between children with and without cow's milk protein allergy: a systematic review with meta-analysis - Zheng, Xueming; Jin, Yi; Luo, Jianhong; Jiang, Fan; Zhang, Limin; Wang, Xiaoxue; Zhang, Hui; Ma, Shaofei; Li, Yejuan (Frontiers in Pediatrics, 2025)
BackgroundVitamin D plays an important role in modulating immune responses, which may be associated with cow's milk protein allergy (CMPA). This meta-analysis aimed to comprehensively compare the vitamin D level between children with CMPA and healthy controls.MethodsStudies comparing the vitamin D level between children with CMPA and healthy controls were comprehensively searched in PubMed, Web of Science, Embase, Wan Fang, CNKI, and VIP until April 2025.ResultsA total of 12 studies, involving 605 children with confirmed CMPA (CMPA group) and 558 healthy controls (control group) were included. The vitamin D level was lower in the CMPA group than in the control group [standardized mean difference (SMD) (95% confidence interval): −1.229 (−2.117, −0.340), P = 0.007]. Regarding subgroup analysis, the vitamin D level was lower in the CMPA group than in the control group in studies using mass spectrometry or automated immunoassay (P = 0.042), and was of no difference in those using enzyme-linked immunosorbent assay (P = 0.200) or chemiluminescence (P = 0.097). Moreover, the vitamin D level was lower in the CMPA group than in the control group in studies conducted in Asia (P < 0.001) or South America (P = 0.041), but not in studies conducted in Europe (P = 0.500). All included studies were high-quality. No publication bias was found. Sensitivity analyses indicated high robustness of the results.ConclusionVitamin D is decreased in children with CMPA, indicating its potential association with CMPA. These findings may enhance the understanding of CMPA and guide the prevention or management of CMPA in children.